Kesalahan Mahasiswa dalam Menyelesaikan Soal Statistika Deskriptif - Chusna, Cahya Amalia (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
This research aims to analyze student errors in solving descriptive statistics questions. The results of this analysis serve as information for researchers in improving learning and finding solutions for students to overcome their problems. This research was conducted at the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) of the Khozinatul Ulum Blora Islamic Institute. The subjects in this research were 10 students who were given a test in the form of a description. The results of this research were: 1) two students made mistakes presenting data in diagram form; 2) as many as four students made inconsistencies in using mathematical symbols. And 3) as many as four students made errors in calculating and errors in using formulas. Meanwhile, most students are able to understand the concepts of descriptive statistics courses, but are still less careful in carrying out calculations and using symbols